Switchable Copper-Catalyzed Cascade Synthesis of Thiazolidine-2-thiones and Thiazole-2(3H)-thiones - Weng, Jian-Quan; Yue, Bin-Jie; Xu, Meng; Yang, Yu-Kun; Jin, Hong-Wei (Synthesis, 2015)
A novel copper-catalyzed cascade synthesis of thiazolidine-2-thiones from N-(2-bromoallyl)amines and carbon disulfide has been developed. The procedure combines carbamodithioic acid formation and copper-catalyzed intramolecular S-vinylation in one sequence. By elevating the temperature, the one-pot reaction efficiently affords thiazole-2(3H)-thiones in moderate to good yields.
Keywords: copper catalyst; carbon disulfide; thiazole synthesis; cascade process